Utility of mean sphered cell volume and mean reticulocyte volume for the diagnosis of hereditary spherocytosis. Issue 7 (9th August 2018) - Arora, Rahul Darshan; Dass, Jasmita; Maydeo, Seema; Arya, Vandana; Kotwal, Jyoti; Bhargava, Manorama
ABSTRACT: Introduction: Hereditary spherocytosis (HS) is the most common congenital hemolytic anemia, characterized by anemia, jaundice, and splenomegaly. The diagnosis of HS relies on symptoms of hemolysis, a family history of HS, and a positive laboratory test which is usually the osmotic fragility test (OFT). We conducted a study to assess the utility of mean corpuscular hemoglobin concentration (MCHC), mean corpuscular volume (MCV), mean sphered cell volume (MSCV), and mean reticulocyte volume (MRV) in the diagnosis of HS and if these are helpful in distinguishing cases of HS from immune hemolytic anemia. Methods: A total of 102 patients suspected to have HS were enrolled. In addition 10 cases of immune hemolytic anemia (IHA) were included in the study and performance of the above screening tests was evaluated. The diagnosis of HS was based on incubated OFT, eosin 5′-maleimide (EMA) dye binding test, and flowcytometric OFT. Results: A total of 29 patients were diagnosed as having HS. The sensitivity and specificity for diagnosis HS by MCHC > 35 g/dL was 44.82%, and ΔMCV−MSCV > 10 fL has a sensitivity and specificity of 82.75% and 95.9% for diagnosis of HS. Using an algorithm of ΔMCV−MSCV > 10 fL and ΔMRV−MSCV < 25, for the differentiation of HS from IHA had sensitivity of 68.9% and specificity of 98.8%.